Planting domains under climate change for Eucalyptus pellita and Eucalyptus urograndis in parts of China and South East Asia. Issue 1 (2nd January 2017) - Booth, T. H.; Jovanovic, T.; Arnold, R. J.
ABSTRACT: A preliminary assessment of climate change impacts on planting domains is presented for Eucalyptus pellita and the E. urophylla x E. grandis hybrid in parts of China and south-east Asia. Simple descriptions of climatic requirements are verified and, where necessary, refined. Climate data for current conditions and projected temperature rises of 1.10, 1.96 and 3.83°C (means across the study area compared against a 1986–2005 baseline) are then used to map at a 10-minute (about 18 km) resolution areas that are likely to have suitable climatic conditions for growing these species in the future. For E. pellita a 1.10°C temperature rise has little impact on climatically suitable areas, while E. urophylla x E. grandis may lose some currently suitable areas in southern China and Sumatra. If temperatures rise by more than 2°C, then larger currently suitable areas will fall outside the range of climatic conditions that are known to be suitable for the two taxa. The vulnerabilities of eucalypt plantations of the two taxa across the study region are generally low, as the short rotation lengths used should allow managers to adapt plantations relatively easily to changing conditions. While this preliminary analysis suggested climate change risks are manageable, the analysis highlighted two risks that are worthy of more detailed research: some existing E. urophylla x E. grandis plantations in lowland areas in Sumatra appear to experience similar climatic conditions to those where leaf diseases have been experienced in Brazil, and extreme frost risks exist in inland areas of southern China.